Measuring use patterns among Malaysian neighbourhood parks users - Abdul Malek, Nurhayati (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
This study validates the use pattern scales of park users' for Neighbourhood Parks context in Malaysian residential area. Samples of 414 daily park users in two neighbourhood parks in the Klang Valley area were achieved. The measures on use pattem were developed using three use pattern scales which are activities, passive activity and active activity. Confirmatory factor analyses (CFA) were used to validate the instrument. Results showed good-fit indices on each construct confirming the theory behind each and every items used in the study. Despite several reduction on the items, the CFA on use pattem yield a good intemal consistencies making it suitable for it's use in the research design as well as future research focusing in measuring the use pattem aspect of neighbourhood green.